The settlers of Talacogon a year after. - University of the Philippines. Community Development Research Council; Committee on the Mindanao Agricultural Resettlement Agency Project (Quezon City Committee on the Mindanao Agricultural Ressetlement Agency Project, Community Development Research Council, University of the Philippines, 1972)
This is a comparative analysis of some pertinent questions which were asked of the settlers in the first baseline survey of 1970 and repeated in the second baseline survey of 1971. The main objective here is to find out whether there has been any change in the lives of the settlers as they try to make resettlement life a success.
Keywords: Migration, Internal -- Asia; Land settlement -- Asia